Optimization of Work Safety Application of Child Ship to Prevent Work Accidents at Km. Ciremai - Meilinasari N; Hutagao l; Laila Puspitasari A; Fierdiana Adella Putri (Dinasti Publisher, 2022)
Along with the times and technological advances that are increasingly advanced, so is the case in the world of shipping, especially maritime technology. As we all know that the equipment on board the ship is now more sophisticated and modern. The equipment is intended to improve the quality and safety of workers on board. With more modern safety equipment, it is hoped that accidents that often occur can be avoided, both shipping safety, work safety, and others. In addition, work safety is influenced by the level of knowledge and discipline of crew members in the use of work safety tools. Most of the accidents that occurred on board the ship were caused by the actions or actions of humans themselves. In this case, especially the crew who do not understand or do not meet the provisions on safety which are usually due to the undisciplined crew of the ship in using the work safety tools on board. The purpose of this study was to find out how to improve the discipline of crew members in the use of work safety equipment and to find out how to improve supervision by officers of crew members in implementing work safety procedures. This research was conducted in KM. Ciremai which is one of the ships managed by PT. Pelayaran Nasional Indonesia (PELNI). The research method used is descriptive qualitative. Sources of data obtained from the research site by means of observations, interviews with officers and crew members, especially the deck and documentation. From the results of the analysis of the data description based on the facts and available data, it shows that the accident on board the ship is influenced by the lack of discipline of the crew in the use of work safety equipment because not a few crew members underestimated the function of the safety equipment. This causes a high rate of work accidents on ships. Apart from the crew's own factors, work accidents can occur from the ship's environmental factors. When the author made observations directly on KM. Ciremai shows that the level of supervision from officers to crew members is still low regarding the application of safety procedures on board ships. So that the solution to the problem that can be done is by holding safety meetings (safety, meetings) on a regular basis. In this safety meeting, films about work safety can be shown to increase the knowledge of workers in order to inform the risks that can occur if they do not work according to work safety procedures. In an effort to overcome the lack of supervision of the ship's crew regarding the application of the use of safety equipment according to workplace safety standards, it can be done by adding CCTV installations in the area outside the ship's deck. So that it can assist officers in supervising the crew while working to ensure the crew is working in accordance with work safety procedures. In addition, ship officers must monitor the CCTV screen on a regular basis so that officers can immediately reprimand crew members who work not according to work safety procedures so that this does not happen again. So it can be concluded that work accidents that occur on ships can be prevented by increasing the discipline of crew members in the use of work safety equipment and knowing the importance of the role of officers to supervise and provide direction as an anticipatory measure for work accidents.